Automated Compliance Enforcement in Multi-Cloud Database Environments: A Comparative Study of Azure Purview, AWS Macie, and GCP DLP - Veeravenkata Maruthi Lakshmi Ganesh Nerella, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
multi-cloud database compliance enforcement Automated compliance enforcement of databases accessed on multi-cloud platforms is needed to address changing regulatory requirements in dynamic cloud architecture. The lightning speed of the introduction of cloud computing has reshaped mode of data management and storage in organizations, making it more scalable, flexible, and cost-effective. But, with the growing application of multi-cloud infrastructures with more than one cloud service provider, including Amazon Web Services (AWS) and Microsoft Azure, and Google Cloud Platform (GCP), the action has brought about intricate issues regarding data compliance, regulatory conformity, and data security techniques. This paper will offer a detailed examination of data compliance in multi-cloud architecture along with the significant regulatory frameworks including GDPR and HIPAA, and the obstacles met during the structural integration and migration in multi-cloud. It also underlines the need to automate compliance to meet a changing regulatory environment and to mitigate the risk of operations. Additionally, the paper attributes AWS, Azure, and GCP along various fronts such as pricing, performance, security, usability, and data management to help organizations make superior decisions on their cloud adoption. Lastly, it draws roadmaps toward more compliance management with AI-based automation and blockchain-based audit, where future goals will focus on improving transparency and resiliency of the distributed cloud platforms.
Keywords: Cloud computing; data compliance; multi-cloud; GDPR; HIPAA; AWS; Microsoft Azure; GCP; cloud migration